Pengaruh Acetobacter xylinum dan Ekstrak Kacang Hijau (Phaseolus radiatus L.) terhadap Produksi Nata dari Substrat Limbah Cair Tahu - George M. Souisa; B. R. Sidharta; F. Sinung Pranata (Universitas Atma Jaya Yogyakarta, 2006)
Industrial waste-water has become a serious problem nationwide. However, one type of waste-water, i.e. tofu waste-water (whey), can be utilized as the source of nata de soya production. This present research is attempts to reveal the effect of various concentrations of inocula and green-bean extracts on nata productions from tofu waste-water. Ten combinations of treatment were applied and coded as A1 – A10. The parameters observed included physical and chemical characters of nata and nitrogen (N) contents. The results show that the increase in concentration of N and inocula will follow by the increase of water content, fiber content, plasticity, and N content of nata de soya produced. Highest thickness of nata was gained at 200 g/L concentration of green-bean extract and 100 ml/L concentration of inoculum.